POLA JUMLAH TROMBOSIT PENDERITA DEMAM BERDARAH DENGUE (DBD) PADA ANAK-ANAK YANG PETANDA SEROLOGINYA POSITIF - Ngurah Subawa, Anak Agung; Sutirta Yasa, I Wayan Putu (journal of internal medicine; Vol. 8, No. 3 September 2007)
Thrombocytopenia represent one of non specific laboratory criterion to uphold diagnosed DHF specified by WHO. Existence of trombositopenia on third or fourth days of disease, will be easily diagnosed of DHF. To know the pattern of the thrombocyte amount on children suffering from DHF based on IgG and IgM serologic marker. This Research is retrospective study by seeing medical report of pediatric patient which is taken care by DHF in Sanglah Hospital Denpasar from July 2005 until June 2006. There are 42 pediatric patient suffering from DHF with the positive serologi examination result, as much 17 child (40.5%) by IgG is positive, 9 child (21.4%) IgM positive and 16 child (38.1%) by IgG and IgM positive. At fourth days of disease development, the mean of the thrombocyte amount in serologi IgG are positive is the lowest (99.8 x 103/mm3). At fifth days, the mean of thrombocyte amount in serologic IgG and IgM are positive is the lowest (61.7 x 103/mm3). At sixth days, the mean thrombocyte amount in serologic IgG are positive is the lowest (61.9 x 103/mm3). At seventh days, the patient having positive IgG or positive IgG and IgM, the mean of the thrombocyte amount experience of the improvement from previous day. At eighth days, patient having positive IgG and IgM were more often have the thrombocyte amount more than the other (only IgG or IgM positive). The patient suffering from second infection (IgG positive or IgG and IgM positive) at the acute phase more often have the thrombocyte amount is lower the than the primary infection (IgM Positive). Expected of continuation research with the sample amount and scope is more than before.
Keywords: serologic marker, thrombocyte, dengue hemorrhagic fever